Anthrone derivatives from the terrestrial actinomycete, Actinomadura sp. BCC47066. (June 2018) - Bunbamrung, Nantiya; Supong, Khomsan; Intaraudom, Chakapong; Dramae, Aibrohim; Auncharoen, Patchanee; Pittayakhajonwut, Pattama
Graphical abstract: Highlights: Eight unknown anthrones were isolated from Actinomadura sp. BCC47066. Compounds were elucidated based largely on spectroscopic data. Compounds were evaluated for antimicrobial activity and cytotoxicity. Abstract: Eight new anthrone derivatives, which are (+)-oxanthromicins E (1 ), F (4 ), and G (5 ), (±)- hemi -oxanthromicin D (2 ), azanthromicin A (7 ), adxanthromicin A2 (10 ), 3-methoxy oxanthromicin (11 ), and (±)-oxanthromicin G (13 ), along with eight previously described compounds (6, 8, 9, 12, 14 –17 ) have been isolated from the terrestrial actinomycete, Actinomodura sp. BCC47066. The chemical structures have been determined on the basis of NMR spectroscopic information and chemical degradation. The configurations were assigned based upon CD spectral analyses, compared with the related compounds. Furthermore, the isolated compounds were assessed for biological activity. Compounds10, 12, and16 showed anti- Bacillus cereus with IC50 in a range of 1.56 − 12.50 μg/mL, while compounds10 and12 exhibited anti-phytopathogenic activity against Colletotrichum capsici and C. gloeosporioides with equal IC50 value of 6.25 μg/mL. All tested compounds possessed low cytotoxicity against both malignant and non-malignant cells.